Photography tour to Inari: the new product development - Volkova, Yulia (HAAGA-HELIA ammattikorkeakoulu, 2013)
The goal of this thesis is to develop a new product for the travel company Fintur Ltd. The demand for a new-product development arises from the Fintur's increasing need to enlarge its product suite. Fintur Ltd. has acted as a commissioning party in this the-sis, as it has an interest in the fully developed product. The product idea consists in offering a nature-based tour combined with photography activities for Russian customers. The tour concept strongly corresponds to Fintur's line of activity and company's business mission. The theoretical framework for the photography tour development has two parts. The first one is concerned with the nature-based tourism definition and its importance in Finland. The second part embraces the theoretical base for a new product develop-ment, namely nature-based tourism product definition, a new product development process description, as well as e-marketing theory. The practical part of the thesis includes the description of actual product development process for Fintur Ltd. Based on the theoretical framework, the photography tour was analysed from the component point of view, and different product levels were consid-ered. The product development process described in the theoretical part was adjusted according to Fintur' case. As the result the company was provided with the fully devel-oped product including the e-marketing plan for the first period.